Industri Halal dan Ekonomi Digital : Peluang Bisnis dan Karir di Masa Depan - Herman, Sebastian (Tamkin Jurnal Pemberdayaan Tazkia, 2023)
This community service aims to socialize future business and career opportunities in the halal industry and digital economy to 12th grade high school students at 5 Islamic schools spread across 3 districts in West Sumatra Province. In addition, this activity also aims to socialize the Tazkia Islamic Institute. This activity was carried out in the form of an offline seminar at the five schools.